PRODUCTION OF HIGH ANTIOXIDANT WINE COFFEE THROUGH SECOND FERMENTATION USING LACTIC ACID BACTERIA - Anbar Istiadi, Khaerunissa
Indonesia is the fourth largest coffee producing country in the world. Indonesian coffee has a variety of flavors and has a positive effect on health due to the presence of antioxidant compounds. These flavors and antioxidant compounds can be increased through the green bean fermentation process using Lactobacillus plantarum. Previous studies have shown that the fermentation process of wine coffee using selected bacterial and yeast isolates is able to change the flavor of the coffee produced. In this research, a second fermentation of wine coffee was done to improve the flavor and antioxidant content. Green bean wine coffee is fermented using the Solid State Fermentation method with variation of L.plantarum inoculum percentage 5% (v / w), 7.5% (v / w) and 10% (v / w) as well as the fermentation time period of 4 hours, 8 hour and 12 hours at 37oC. Optimum age of L.plantarum used is 6 hours. During the fermentation process, total microbial counts, pH, polyphenol levels with Folin-Ciocalteau reagent, and antioxidant activity with DPPH reagents was measured. The fermented green bean then roasted to medium level. Roasted bean were analyzed through cupping tests, and measurements of polyphenol levels and antioxidant activity were done. During the fermentation process, the total number of microbes increases until the 8th hour and then enters the stationary phase until the end of the fermentation. Total polyphenol levels in fermented green bean have increased up to 2% compared to controls. The antioxidant activity of fermented green bean increased up to 19%. The highest increment in polyphenol levels in fermented green bean from 3.23% to 5.76% and antioxidant activity from 23.62% to 42.87%. The highest total polyphenol levels and antioxidant activity were obtained in 12 hours fermented green bean with the addition of 10% (v / w) inoculum. Roasting process causes a decrease in polyphenol levels and antioxidant activity in the control and all fermentation treatments. The cupping test results showed that the green bean fermented by addition of 10% inoculum for 8 hours had the highest value of 80.75 so that it was included in specialty coffee. This research shows that the second fermentation process using L.plantarum is able to change flavor and maintain winey flavor , increase the total polyphenols and antioxidant activity of wine coffee.